Evaluation of clinical formalin‐fixed paraffin‐embedded tissue quality for targeted‐bisulfite sequencing. Issue 2 (17th December 2020) - Ohmomo, Hideki; Komaki, Shohei; Ono, Kanako; Sutoh, Yoichi; Hachiya, Tsuyoshi; Arai, Eri; Fujimoto, Hiroyuki; Yoshida, Teruhiko; Kanai, Yae; Sasaki, Makoto; Shimizu, Atsushi
Abstract : Formalin‐fixed paraffin‐embedded (FFPE) tissues are promising biological resources for genetic research. Recent improvements in DNA extraction from FFPE samples allowed the use of these tissues for multiple sequencing methods. However, fundamental research addressing the application of FFPE‐derived DNA for targeted‐bisulfite sequencing (TB‐seq) is lacking. Here, we evaluated the suitability of FFPE‐derived DNA for TB‐seq. We conducted TB‐seq using FFPE‐derived DNA and corresponding fresh frozen (FF) tissues of patients with kidney cancer and compared the quality of DNA, libraries, and TB‐seq statistics between the two preservation methods. The approximately 600‐bp average fragment size of the FFPE‐derived DNA was significantly shorter than that of the FF‐derived DNA. The sequencing libraries constructed using FFPE‐derived DNA and the mapping ratio were approximately 10 times and 10% lower, respectively, than those constructed using FF‐derived DNA. In the mapped data of FFPE‐derived DNA, duplicated reads accounted for > 60% of the obtained sequence reads, with lower mean on‐target coverage. Therefore, the standard TB‐seq protocol is inadequate for obtaining high‐quality data for epigenetic analysis from FFPE‐derived DNA, and technical improvements are necessary for enabling the use of archived FFPE resources.